High Expression of IL-36γ in Influenza Patients Regulates Interferon Signaling Pathway and Causes Programmed Cell Death During Influenza Virus Infection - Liu, Shuai; Li, Hui; Wang, Yeming; Li, Haibo; Du, Sisi; Zou, Xiaohui; Zhang, Xulong; Cao, Bin (Frontiers in Immunology, 2020)
As a severe complication of influenza infection, acute respiratory distress syndrome (ARDS) has higher morbidity and mortality. Although IL-36γ has been proven to promote inflammation at epithelial sites and protect against specific pathogen infection, the detailed roles in severe influenza infection remain poorly understood. In this study, we have found that the expression of IL-36γ is higher in influenza-induced ARDS patients than healthy individuals. IL-36γ was induced in human lung epithelial cells and peripheral blood mononuclear cells by Influenza A virus (IAV) infection, and its induction was synergistically correlated with initiation of the cyclooxygenase-2 (COX-2)/Prostaglandin E2 (PGE2) axis. We also have found that expression of superficial IL-36R was elevated in severe influenza patients and in IAV-stimulated cells. Furthermore, although IL-36γ enhanced the induction of type I and III interferons (IFNs), which promoted IAV-mediated IFN-stimulated STAT1 and STAT2 phosphorylated inhibition in lung epithelial cells, the downstream interferon-stimulated genes (ISGs) were not affected. Finally, we have revealed that IL-36γ treatment could promote apoptosis and inhibit autophagy in the early stages of IAV infection. Overall, these findings demonstrated IL-36γ is a critical host immune factor in response to IAV infection. It has potential activity in the regulation of the interferon signaling pathway and was involved in different types of programmed cell death in human airway epithelial cells as well.